Light fastness of printing inks: A review - Aydemir, Cem; Yenidoğan, Semiha (Journal of Graphic Engineering and Design, 2018)
Light fastness, in its broadest sense, is the resistance of colours to fading under the influence of a light source. Light fastness is one of the most important physical, and therefore visual, properties sought in both pigments and in the inks. Artificial and natural light causes most pigments to fade resulting in colour change. The light fastness of inks is important especially in the packaging and advertising industries. The posters and advertisements hung on the billboards used especially in outdoor advertising, printed product packaging and other printed products exposed to sunlight require high degree of light fastness. In this study, light fastness and factors affecting the resistance of the colour to the light were investigated and suggestions were made regarding high light fastness in terms of printability.